An experimental program for physical education of rugby players at the stage of specialized basic training - Artur Martyrosyan; Vladlena Pasko; Anatoliy Rovnyi; Volodymyr Ashanin; Volodymyr Mukha (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to develop a program of general physical training of rugby players at the stage of specialized basic training and to investigate the dynamics of indicators of general physical preparedness using computer technology. Material & Methods: study involved 60 athletes aged 16-18 years. Results: content of the comprehensive program of general physical training of rugby athletes at the stage of specialized basic training and the results of an experimental verification of its implementation are presented. Conclusion: in the course of the pedagogical experiment, the effectiveness of using the developed experimental program for improving the training process of rugby players of 16-18 years is proved, which is confirmed by the results of the research.